Healthful workplace facilities and work stress among academic staff of UiTM Jengka, Pahang / Mas 'udah Asmui, Adibah Hussin and Dr. Halil Paino - Asmui, Mas 'udah; Hussin, Adibah; Paino, Halil (2013)
In any organizations, a healthful workplace facility brings safety to employees' physical and mental capabilities especially in performing their daily routine works. In order to reach the healthful workplace. providing healthful facilities must be taken into account. For example, an efficient humidity and comfortable workstation could provide good working conditions to academic staff. A good working condition also creates enjoyment of working habits for the academics staff especially in situation before and after lecturing. From 204 number of population only 34 respondents from academic staff. UiTM Pahang responded and completed questionnaires comprised demographic section, work environment factors section and work stress section. The data was analysed using SPSS 20. 0 for windows. Descriptive statistics and multiple regressions were used as the scale of measurements of this study. Results exhibited majority academic staff who responded was women at young age and worked for UiTM Jengka Campus less than five years and in rank of grade DM45 (Degree in Master holders). Results also showed the four workplace facilities have been provided by UiTM Jengka Campus towards its academic staff with mean more than 3.0. However. chair seating's mean is the lowest among them (M = 3.338). The workstation and chair seating were found as negative correlation and contributed significantly to work stress (54.2 percent). These findings demonstrated that work stress happened among academic staff in UiTM Jengka Campus in the context of lacking providing healthful workplace facilities. Work stress exists when there is discrepancy between working condition and human systems in workplace.